PENGARUH PENGGUNAAN METODE ASOSIASI KATA TERHADAP PENINGKATAN HAFALAN MAKNA MATERI ASMAUL HUSNA PAI KELAS VII - Rohmatul Ummah; Muhammad Adi Prastyo; Muhammad Ali Rohmad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The low ability of students to memorize the meaning of the vocabulary of Asmaul Husna indicates that the ongoing learning process has not been optimal in increasing the activeness and level of confidence in students when answering questions during the learning process. This study aims to analyze the improvement of the ability to memorize the meaning of Asmaul Husna in grade VII students through the application of the word association method. Two cycles were implemented in the Classroom Action Research (CAR) approach, which includes the planning stage, action implementation, observation, and reflection. The subjects of this study were grade VII D students selected using a purposive sampling technique. Data collection was carried out through pre-test, post-test, observation, and documentation. It was shown that the results of the study using the word association method were effective in improving students' memorization abilities. This can be seen from the increase in students' average score, namely from 52.40 when the pre-test was carried out to 96.80 when the post-test was carried out, with a significance value of 0.000 (<0.05). In addition to improving learning outcomes, this method also makes students more active, enthusiastic, and confident during learning. The word association method is an effective, interesting, and meaningful learning strategy to improve the ability to memorize the meaning of Asmaul Husana in grade VII students. ABSTRAK Rendahnya kemampuan siswa dalam menghafal makna kosakata Asmaul Husna menunjukkan bahwa proses pembelajaran yang berlangsung belum optimal dalam meningkatkan keaktifan serta tingkat percaya diri dalam siswa ketika menjawab pertanyaan selama proses belajar. Penelitian ini bertujuan untuk menganalisis peningkatan kemampuan menghafal makna Asmaul Husna pada siswa kelas VII melalui penerapan metode asosiasi kata. Dilaksanakannya dua siklus dalam pendekatan Penelitian Tindakan Kelas (PTK), yang meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek dari penelitian ini merupakan siswa kelas VII D yang dipilih dengan teknik purposive sampling. Pengumpulan data dilakukan melalui pre-test, post-test, observasi, serta dokumentasi. Ditunjukkan bahwa hasil penelitian dengan menggunakan metode asosiasi kata efektif dalam meningkatkan kemampuan hafalan siswa. Hal ini terlihat dari nilai rata-rata siswa yang meningkat, yaitu dari 52,40 ketika pre-test menjadi 96,80 dilakukannya post-test, nilai signifikansi sebesar 0,000 (< 0,05). Selain meningkatkan hasil belajar, metode ini juga membuat siswa untuk lebih aktif, antusias, dan percaya diri selama dilakukannya pembelajaran. Metode asosiasi kata merupakan strategi pembelajaran efektif, menarik, dan bermakna untuk meningkatkan kemampuan menghafal makna Asmaul Husna pada siswa kelas VII.